ANALYSIS OF USER SATISFACTION IN THE IMPLEMENTATION OF ONLINE TICKET ORDERING SYSTEM AT LEMBAR FERRY PORT, WEST NUSA TENGGARA PROVINCE - Sulistiyono, Noor; Susanto, Novi Tri; Kartini, Sri; Setiawan, Bambang; Sidharta, Driaskoro Budi; Ahmad, Jeannova Shabilla (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2024)
Lembar Ferry Port is a very important commercial port in developing and connecting West Nusa Tenggara Province, especially Lombok Island with Bali Province. This makes the port management as a service provider industry continue to strive to develop services to increase the potential of the port and the satisfaction of service users, one of which is the online ticket booking system. This study aims to analyze the level of service user satisfaction with the implementation of the online ticket booking system using the Customer Satisfaction Index (CSI) method at Lembar Ferry Port as one of the providers of ferry transportation services on Lombok Island. Data collection was conducted by distributing questionnaires to users of Lembar Ferry Port services as respondents to obtain data on the level of expectations and performance felt by service users. Based on the results of the study, service users have felt quite satisfied with the performance of the online ticket booking system carried out by the management of Lembar Ferry Port. This can be seen from the CSI value obtained, which is 59.12%. The things that need to be improved or corrected from the online ticket booking system at Lembar Ferry Port, one of which is the system display for service users which is simple but still informative because it has the highest expectation value from service users.